The impact of variation and autonomy on psychological responses to high intensity interval training exercise. (May 2022) - Mastrofini, Gianna F.; Collins, Robert P.; Rosado, Alanis P.; Tauran, Ralph C.; Fleming, Abby R.; Kilpatrick, Marcus W.
Abstract: Introduction: High-intensity interval training (HIIT) provides notable physiological benefits and is generally well-tolerated across modalities and populations. This study investigated how exercise autonomy support impacts psychological responses to exercise. Methods: Twenty-nine participants completed three HIIT trials: Conventional-HIIT with 60-sec work segments, Varied-HIIT with a mix of 30, 60, 90, & 120-sec segments, and Autonomous-HIIT with self-selected 30, 60, 90, & 120-sec segments. Affective valence, enjoyment, and intention were measured. Results: Affective valence during exercise was not different between trials (p > 0.05) but enjoyment during exercise was higher for Autonomous-HIIT (p < 0.05). Enjoyment and intention measured post-exercise were greater for Autonomous-HIIT than Varied-HIIT (p < 0.05). Conclusion: Autonomous HIIT produced more desirable responses than varied and traditional HIIT sessions. These data suggest that HIIT sessions utilizing self-selected interval durations can produce more positive responses, which provides the basis for recommending autonomy within HIIT exercise. Highlights: - Autonomous HIIT exercise was less effortful than conventional HIIT exercise. - Affective responses were positive for all HIIT exercise sessions. - Autonomous HIIT exercise was more pleasurable than varied HIIT exercise. - Provision of autonomy during HIIT exercise is advisable.